From Evolved Stars to the Formation and Evolution of NGC 6822 - Sima Taefi Aghdam; Elham Saremi; Atefeh Javadi
NGC6822, an isolated dwarf irregular galaxy (dIrr), due to close distance, apparent isolation, and easy observation, has been always selected as a desired candidate for studying star formation and galactic evolution, without the strong gravitational in uences of other systems. To derive the SFH of NGC6822, the method mentioned by Javadi et al. (2011) is used which is based on theoretical models coupled with color-magnitude diagrams (CMDs) by using directly the long period variable (LPV) stars which are mostly asymptotic giant branch (AGB) stars at their very late stage of evolution, as well as more massive red super-giant (RSG) stars according to their significant role to study the star formation rate (SFR). To calculate the SFH in the bar of the galaxy, we use more than 600 LPV stars from different catalogs of variable stars that two of the most important are Whitelock et al. (2013) and Letarte et al. (2002) that they reported the main part of the LPVs and the Carbon stars, respectively, Patrick et al. (2015) announced the RSG stars. Understanding the star formation history of NGC 6822 plays an important role in comparing the galaxy history evolution with other nearby dwarf galaxies as well as studying the nature of the evolving population of galaxies which were detected in deep redshift surveys.
Keywords: Astronomy